The Role of Individual Capacity, Motivation, Skill and Expertise on Managerial Performance (Study on Government Organizations in Metro, Lampung) - Nur Hamid; Taufik Taufik; Komaruddin Komaruddin (Prosiding International conference on Information Technology and Business (ICITB), 2020)
The purpose of this study was to examine the effect of the Role of Individual Capacity, Work Motivation, and Skills on Managerial Performance (Study on Government Organizations in Metro, Lampung). The independent variables in this study were the role of individual capacity, motivation, skill, and expertise. The dependent variable was Managerial Performance. The population and sample of this study were the financial division employees of local government organizations in Metro, Lampung. The analytical method used Multiple Linear Regression Analysis. This study used SPSS version 20. Based on the result, it showed that the role of individual capacity had an effect on managerial performance, work motivation had an effect on managerial performance and abilities, and expertise had no effect on managerial performance.Keyword: The Role of Individual Capacity, Work Motivation, Skill, Expertise, Managerial Performance